MONITORING OF FLUORIDE AND IODIDE LEVELS IN DRINKING WATER USING ION SELECTIVE ELECTRODES - Ahmed, R.; Nisa, Viqar -un-; Hussain, M.; Tanwir, R.; Qureshi, S. A. (The Nucleus, 2020)
Fluoride and iodide, the most important constituents of drinking water are essential as well as toxic depending on their levels. For their analysis in water mostly ion-selective electrodes, spectrophotometry, titrimetry and coulometry etc; have been used and literature has been briefly reviewed. Ion-selective electrodes offer an efficient method for the measurement of the two halides and were mostly used during this work. Fabrication of these electrodes is briefly described. Comparison of results obtained by ion selective electrode and coulometry is given. Recoveries of the added fluoride ions from the samples were good. A large number of water samples from Rawalpindi-Islamabad area were analyzed for fluoride and iodide. Levels of fluoride and iodide from two main water reservoirs of Rawalpindi and Islamabad are reported before and after treatment. Both surface and ground water samples were analyzed and results are compared and discussed. Some samples from northern areas were also analyzed for iodide and fluoride and compared. Intake of fluoride and iodide from water of different areas is also compared. Water samples, which caused bone deformation in certain areas in Punjab due to excess fluoride, were also analyzed for fluoride and results are presented.